Changing fortunes : biodiversity and peasant livelihood in the Peruvian Andes - Zimmerer, Karl S. (California studies in critical human geography ;, 1996)
This title provides a study of the relationship between crop plant biodiversity, peasant behaviour, and the larger society, and dispells some long held assertions about Andean farming.